Higher Bacterial Diversity of Gut Microbiota in Different Natural Populations of Leafhopper Vector Does Not Influence WDV Transmission - Wang, Hui; Wu, Nan; Liu, Yan; Kundu, Jiban Kumar; Liu, Wenwen; Wang, Xifeng (Frontiers in Microbiology, 2019)
The bacterial communities in the gut of an insect have important ecological and functional effects on the insect. However, the community composition and diversity of the gut microbiota in insects that vector plant viruses are poorly understood. As an important insect vector, Psammotettix alienus transmits various viruses including wheat dwarf virus (WDV). Here, we used the combination of leafhopper and WDV as model to survey the influence of gut microbiota on virus transmission characteristic of insect vector and vice versa. We have characterized 22 phyla and 249 genera of all gut bacterial communities in the leafhopper populations collected from six geographic regions in China. Community composition and diversity varied across different geographic populations. However, WDV transmission efficiencies of these six field populations were all greater than 80% with no significant difference. Interestingly, the transmission efficiency of WDV by laboratory reared insects with decreased gut bacterial diversity was similar to that of field populations. Furthermore, we found that the composition of the leafhopper gut bacteria was dynamic and could reversibly respond to WDV acquisition. Higher bacterial diversity and abundance of gut microbiota in different leafhopper populations did not influence their WDV transmission efficiency, while the acquisition of WDV changes gut microbiota by a dynamic and reversible manner. This report provides insight into the complex relationship between the gut microbiota, insect vector and virus.